Republic of Kosovo : 2018 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
The near-term outlook is broadly positive, with robust growth and low inflation. However, growth potential remains constrained by weak external competitiveness, high informality, low labor force participation, and a large infrastructure gap. In a complex political environment, the structural reform progress has been slow and fiscal risks have increased.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Kosovo